Modulação dos efeitos da decisão em direito tributário e segurança jurídica - Kauffman, Karina (2010)
This study aims to analyze the legal and modulation, to verify that the application of the "modulation" provides legal certainty for jurisdictional. Toward that goal, first we aimed at analyzing the role of the judiciary in a democratic state of law. We note that in the modern state, there is no longer a reporting relationship between the political system and legal and that the Judiciary itself as a neutral power capable of guaranteeing the dictates of the Constitution and ensure the fundamental rights of citizens under the aegis of the legality and morality. Legal certainty, we note that from the moment the standard judicial becomes repeatable for similar cases, has emerged as a consolidated jurisprudential understanding, the article approaches the legal norm, but settled case law is not law. Seek in our work show that certainty is a overprinciple, i.e, a principle of overlevel, loaded axiological high and requires other principles for their definition. One consequence of legal certainty that this work will explore the retroactivity of the law, which is closely related to the principle of legality, since it means that the law should be applied to the case is the law in force at the time of occurrence of and the law. If there is some kind of change in position of superior courts, which leads to change its interpretation of the Constitution and laws, such change may not be effective retroactively, on pain of hurt, among other constitutional rules, the objective good faith of courts which relied on the hitherto prevailing law. This is one of the guarantees of legal certainty in the democratic state of law